MOTIVASI MAHASISWA SOSIOLOGI UNTUK MELAKSANAKAN SHOLAT BERJAMAAH DI MUSHOLLA FISIP - Subarka "; Basri " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research was conducted at the Faculty of Social and Political Science, University of Riau Pekanbaru. The purpose of this research was to determined the motivation of students’ Sociology to conducted praying together in the musholla of Faculty of Social and Political Science. To know the influencing and inhibiting factors of the students ’Sociology to conduct praying together in musholla Faculty of Social and Political Science. This research entitled "The Students’ Sociology Motivation to Praying Together In Faculty of Social and Political Science Musholla". The main problem in this research was how the motivation of students’ Sociology to conducted praying together in musholla of Faculty of Social and Political Science and what was the factors that influencing and inhibiting the students’ sociology’ to conducted praying together in Faculty of Social and Political Science musholla. The Sampling in this research was by purposive sampling technique. The total number of population was the students’ of Sociology with different years start from 2013 until 2016. The researcher was taking 10 persons as informants to be interviewed who are randomly selected and with predefined criteria. The Qualitative methods described all the processed that found in the field . The filtering data instruments used was observation, documentation and interview. The result of the research in generally has been done by researcher. According to the researcher, the motivation of Sociology students’ to conducted the praying together in the musholla of Faculty of Social and Political Science was adequate facilities, religious studies and the location of the musholla near to the campus. Because if the third of these motivations can further and increase the number of students’ who praying in Faculty of Social and Political Science musholla. Based on the research that has been done, the influence factors was a factor that can make students’ conduct a certain action. A person can be motivated by several factors that conducted to do something of habits, peers, learning schedules, and also facilities Key word : The Motivation of Praying Together